Identification of a myeloperoxidase - like ortholog from rock bream (Oplegnathus fasciatus), deciphering its transcriptional responses to included pathogen stress - Elvitigala, D. A. S.; Whang, I.; Nam, B. H.; Park, H. C.; Lee, J. (Elsevier, 2015)
Myeloperoxidases (MPOs) are heme-linked oxidative stress-generating enzymes found abundantly in azurophilic granules of polymorphonuclear neutrophils. Mature MPOs act as potent antimicrobial agents by producing hypohalous acids using hydrogen peroxide and halide ions as substrates. These acids can readily oxidize reactive groups of biomolecules on invading microbes. In this study, we identified and characterized a homolog of MPO from rock bream (Oplegnathus fasciatus), designated as RbMPO. We analyzed the RbMPO gene for its basal expression level in physiologically important tissues and for transcriptional changes under different pathogenic stress conditions. The complete coding sequence of RbMPO consisted of 2652 nucleotides encoding an 884 amino acid sequence with a predicted molecular mass of 99.7 kDa. Our in silico analysis confirmed the typical MPO domain arrangement in RbMPO, including the propeptide, large chain and heavy chain, along with the heme peroxidase signature. Intriguingly, a C1q domain was also identified in the C-terminal region of the derived amino acid sequence. Most of the known functionally important residues of MPOs are found to be well conserved in RbMPO, showing a close evolutionary relationship with other teleostan MPOs, particularly with that of mandarin fish. RbMPO exhibited a ubiquitous basal expression in physiologically relevant tissues, with particularly high expression levels in blood cells. Basal transcript levels of RbMPO in gill and spleen tissues were found to change upon different pathogen or pathogen-derived mitogen stimulation, with detectable inductive responses. Together, these data suggest the potential involvement of RbMPO in the innate immune response in rock bream.
Keywords: Rock bream; Myeloperoxidase; Spatial expression; Pathogen stress; Transcriptional modulation